PERSEPSI MASYARAKAT TERHADAP KINERJA APARATUR DESA DALAM PENYELENGGARAAN PEMBANGUNAN DI DESA SUAK RIBEE KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Zulihar Mukmin, Ruslan, Siti Kurniati (Universitas Negeri Malang, 2018)
This article discussed the public understanding of the duties and functions of the civilian apparatus in carrying out development, the public response to the performance of the civil appara- tus in carrying out development, the performance of the apparatus when carried out their duties and functions to carry out development in accordance with the applicable rules. The method used a qualitative descriptive method. Data were collected through interviews with 15 respondents in Suak Ribee. The results of the study showed that in general, the community understood the duties and functions of the civil apparatus. The community acknowledges that the work capacity carried out by the authorities, especially public services, has met public expectations while the quality of work was recognized as good but not maximal due to lack of human resources.DOI: http://dx.doi.org/10.17977/um019v3i12018p106